2015
DOI: 10.1016/j.bbamcr.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Iron –sulfur cluster biogenesis in mammalian cells: New insights into the molecular mechanisms of cluster delivery

Abstract: Iron-sulfur (Fe-S) clusters are ancient, ubiquitous cofactors composed of iron and inorganic sulfur. The combination of the chemical reactivity of iron and sulfur, together with many variations of cluster composition, oxidation states and protein environments, enables Fe-S clusters to participate in numerous biological processes. Fe-S clusters are essential to redox catalysis in nitrogen fixation, mitochondrial respiration and photosynthesis, to regulatory sensing in key metabolic pathways (i. e. cellular iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
180
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(185 citation statements)
references
References 327 publications
(464 reference statements)
3
180
0
2
Order By: Relevance
“…However, a protein docking study further suggested that Yfh1 binding would only be possible with the flexible loop of Nfs1 positioned inside the cysteine substrate-binding site rather than in proximity of the Fe-S cluster assembly site. This implies that iron and sulfur donation would have to occur sequentially and that sulfur donation would require the displacement of Yfh1 from the Fe-S cluster assembly complex (17), which is in contrast with the general consensus that Fe-S cluster assembly requires the simultaneous binding of the scaffold to both the cysteine desulfurase and the iron donor (1,2).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…However, a protein docking study further suggested that Yfh1 binding would only be possible with the flexible loop of Nfs1 positioned inside the cysteine substrate-binding site rather than in proximity of the Fe-S cluster assembly site. This implies that iron and sulfur donation would have to occur sequentially and that sulfur donation would require the displacement of Yfh1 from the Fe-S cluster assembly complex (17), which is in contrast with the general consensus that Fe-S cluster assembly requires the simultaneous binding of the scaffold to both the cysteine desulfurase and the iron donor (1,2).…”
mentioning
confidence: 65%
“…In yeast and animal cells, mitochondria assemble Fe-S clusters autonomously, whereas other cellular compartments depend on precursors and/or signals generated by mitochondria (2). A complete loss of mitochondrial Fe-S cluster synthesis is therefore lethal, while partial defects typically result in mitochondrial dysfunction, multiple Fe-S enzyme deficits throughout the cell, and global iron imbalance (1). In humans, inherited defects in mitochondrial Fe-S cluster synthesis have been linked to the neurodegenerative disease Friedreich ataxia and to various tissue-specific conditions, although the role of this process in human disease is most likely underestimated (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1-2, and b, pp. [1][2][3][4][5][6][7][8], or between monomers from two adjacent trimers (supplemental Table S2 24 complex. A-F, to visualize the structure of the entire complex, the simulated half of the structure was aligned with itself into the EM density map of the refined 3D model.…”
Section: Molecular Dynamics Flexible Fitting For Docked Structures-mentioning
confidence: 99%
“…But these clusters do not pre-exist and are not produced for free. To produce them, we need specialized machines in our bodies, which are made of several different proteins, much like an assembly line [6]. Frataxin seems to be an important part of this assembly line [7,8].…”
Section: What Causes Frda?mentioning
confidence: 99%